2016
DOI: 10.1007/s40801-016-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Economic Impact of the V-Go® Disposable Insulin Delivery Device for Insulin Delivery in Patients with Poorly Controlled Diabetes at High Risk

Abstract: BackgroundDiabetes is a chronic condition and when poorly controlled can lead to complications and death. Patients with glycated hemoglobin (A1C) measures >9 % are at significant risk for diabetes-related complications impacting the patient’s quality of life and imposing higher costs on the healthcare system. A1C reductions of 1 % or greater in this population have demonstrated substantial health and economic benefits. Reducing the percent of patients at risk is an essential component of quality-care measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Patients in the V-Go group reported a 24% reduction in TDD U/day and a 25% reduction in TDD U/kg while patients in the STO group reported no changes in TDD. Our observation of decreased insulin utilization after initiation of V-Go is consistent with previous research 8, [18][19][20]22 and supports the theory that continuous insulin infusion may be more efficient than insulin delivery via single or multiple injections. 14,18 Patients in the V-Go as well as the STO group were generally satisfied with their insulin delivery device at baseline and EOS, with average TRIM-Diabetes Device scores in the 70s and 80s on a 100-point scale.…”
Section: Discussionsupporting
confidence: 92%
“…Patients in the V-Go group reported a 24% reduction in TDD U/day and a 25% reduction in TDD U/kg while patients in the STO group reported no changes in TDD. Our observation of decreased insulin utilization after initiation of V-Go is consistent with previous research 8, [18][19][20]22 and supports the theory that continuous insulin infusion may be more efficient than insulin delivery via single or multiple injections. 14,18 Patients in the V-Go as well as the STO group were generally satisfied with their insulin delivery device at baseline and EOS, with average TRIM-Diabetes Device scores in the 70s and 80s on a 100-point scale.…”
Section: Discussionsupporting
confidence: 92%
“…In a small survey, V-Go was perceived by patients to be easy to use, discreet, and comfortable to wear [ 19 ]. Multiple studies support the effectiveness of V-Go in significantly reducing A1C, demonstrating decreases in mean A1C of 1.2–2.0% [ 16 20 , 28 , 29 ]. In a study by Rosenfeld et al, mean A1C decreased by 1.2% after switching to V-Go, and after V-Go was stopped, A1C increased by 0.6%.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective chart analysis provides an observation of the change in cost and glycemic control when RHI was administered with the V-Go disposable insulin delivery device in a real-world setting. V-Go has proven to be an appropriate therapy for a broad range of patients, resulting in significantly reduced A1C levels ( 19 , 20 ). Stability studies have been conducted for the administration of U-100 RHI with V-Go, and RHI was found to be stable in this delivery device ( 21 ).…”
Section: Discussionmentioning
confidence: 99%